Psychological assessment of sexually abused children and their families - Friedrich, William N. (Interpersonal violence., 2002)
Designed for professionals in the field of child maltreatment, this authoritative book presents a compelling theoretical framework that guide's assessment of children and adolescents who have been sexually abused and their parents. The book is designed to make it easier for clinicians to select a number of measures or procedures across three dimensions that have considerable clinical relevance - attachment, dysregulations, and self-perception. Psychological Assessment of Sexually Abused Children and Their Families features in particular the assessment of sexually aggressive children and an ex.